Optimization of Lovastatin Production from A Local Isolate of Aspergillus terreus A50 in Solid State Fermentation by Classical and Statistical Methods - Al-Sa'ady, Ali J. R.; Aziz, Ghazi M. (Iraqi Journal of Science, 2020)
Lovastatin is one of the most important compounds that is produced from some filamentous fungi, being employed in the reduction of hypocholesterolemia. The results of screening, after the collection of seventy-three local fungal isolates from different areas, demonstrated that the local isolate Aspergillus terreus A50 was the best isolate for lovastatin production, with a concentration of 12.66 µg/ml, through the submerged fermentation. Lovastatin produced from A. terreus A50 showed antimicrobial activities against a Candida albicans isolate. Solid state fermentation (SSF) was the best system to produce the highest yield of lovastatin by A. terreus A50 as compared to the submerged fermentation (SmF) system, with and without agitation. The optimum conditions for lovastatin production by SSF were also determined. The parameters included carbon sources (wastes), carbon sources mixture, incubation temperature, and moisturizing solution, which are commonly used in classical procedures. The results showed that a higher lovastatin production of 102.321 µg/gm substrate was obtained in the culture containing wheat bran and oat bran (1:1 w:w), sodium acetate, moisture ratio of 1.2 v:w, pH 7, incubation temperature of 30 °C and incubation period of 6 days. Some of these parameters, including pH, incubation period, and moisture ratio were determined by utilizing the Response Surface Method (RSM) as a statistical approach.